Determination of mercury speciation in fish tissue with a direct mercury analyzer. (15th April 2013) - Barst, Benjamin D.; Hammerschmidt, Chad R.; Chumchal, Matthew M.; Muir, Derek C.G.; Smith, James D.; Roberts, Aaron P.; Rainwater, Thomas R.; Drevnick, Paul E.
Abstract Knowledge of Hg speciation in tissue is valuable for assessing potential toxicological effects in fish. Direct Hg analyzers, which use thermal decomposition and atomic absorption spectrometry, have recently gained popularity for determining organic Hg after procedural solvent extraction from some environmental media, although quantitative recovery from lipid‐rich materials, such as fish liver, has been problematic. The authors developed a new method by which organic Hg in fish liver and muscle is estimated by the difference between direct measurements of inorganic Hg in an acid extract and total Hg in whole tissue. The method was validated by analysis of a certified reference material (DOLT‐4 dogfish liver) and naturally contaminated fish tissues with comparison to an established Hg speciation method (gas chromatography cold vapor atomic fluorescence spectrometry). Recovery of organic Hg from DOLT‐4, estimated by difference, averaged 99 ± 5% of the mean certified value for methylmercury. In most liver samples and all muscle samples, estimates of organic Hg from the proposed method were indiscernible from direct speciation measurements of methylmercury (99% ± 6%). Estimation of organic Hg by the difference between total Hg and inorganic Hg was less accurate in liver samples with a high percentage of inorganic Hg (90%). This was because of the increased uncertainty that results from estimating a third value (i.e., organic Hg) by using the difference between two large concentrations (inorganic and total Hg). The proposed method is a useful tool for examining the speciation of Hg in fish muscle and liver, and by extension, potentially other tissues and environmental media. Environ Toxicol Chem 2013;32:1237–1241. © 2013 SETAC